Reflections on the Green Growth Index for developing countries: A focus of selected African countries. (29th December 2017) - Kararach, George; Nhamo, Godwell; Mubila, Maurice; Nhamo, Senia; Nhemachena, Charles; Babu, Suresh
Abstract: This article presents a pilot and baseline African Green Growth Index (AGGI). The work is premised on the importance of Africa implementing green growth strategies. Baseline indicators allow countries to monitor progress towards green growth transition. The AGGI incorporates 48 indicators applied to 22 countries that had the requisite data. What emerges is that 18 out of the 22 African countries sampled scored 50 percentage points and above. The countries scoring below this threshold were: Egypt, Algeria, Nigeria and South Africa. The top five countries on the AGGI (as ranked from 1−5) were: Namibia, Zambia, Ghana, Tanzania and Togo. The authors recommend that for wider acceptance across the continent, the AGGI should work towards incorporating all 54 nations.